2010
DOI: 10.1248/bpb.33.707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Celecoxib, a Selective Cyclooxygenase-2 Inhibitor on Carbon Tetrachloride Intoxication in Rats

Abstract: CCl 4 (0.5 ml/kg as CCl 4 ) was orally administered to rats. Twelve hours after administration of CCl 4 , plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, indicators of liver necrosis, were significantly higher than those in the control group showing that active liver necrosis took place. At the same time the level of liver vitamin C was decreased significantly compared to that in the control group. Oral administration of 100 mg/kg each of celecoxib 3 and 8 h after CCl 4 treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…33) Then, it is reasonable that inhibiting only COX-2, a component in this exacerbation cycle, ameliorated hepatitis in the COX-2 transgenic mice 33) as well as in CCl 4 -administered rats. 34) Therefore it is conceivable that the reduced number of Kupffer cells and resulting decrease in TNF-α release intercepted the exacerbation cycle in KO mice.…”
Section: )mentioning
confidence: 99%
“…33) Then, it is reasonable that inhibiting only COX-2, a component in this exacerbation cycle, ameliorated hepatitis in the COX-2 transgenic mice 33) as well as in CCl 4 -administered rats. 34) Therefore it is conceivable that the reduced number of Kupffer cells and resulting decrease in TNF-α release intercepted the exacerbation cycle in KO mice.…”
Section: )mentioning
confidence: 99%
“…COX-2 is expressed only at low levels in normal hepatocytes, whereas it is markedly increased in chronic hepatitis and liver cirrhosis (3,4). It has been reported that the selective inhibitor of COX-2, celecoxib (20 mg/kg/day), reduced hepatic fibrosis in both CCl4-, BDL-and TAA-treated rats (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to this study, opposing results have been reported in CCl 4 models of liver fibrosis. In a short-term model, celecoxib reduced liver inflammation and damage during the early phase of CCl 4 toxicity (Washino et al, 2010). A similar short-term study found that celecoxib reduced markers of lipid peroxidation but had no effect on hepatic toxicity or necrosis (Ekor et al, 2013).…”
Section: Discussionmentioning
confidence: 93%